Microwave-assisted co-pyrolysis of Bamboo biomass with plastic waste for hydrogen-rich syngas production - Saifuddin N.; Priatharsini P.; Hakim S.B. (Science Publications, 2023)
Concerns about diminishing fossil fuels and increasing greenhouse gas emissions are driving many countries to develop renewable energy sources. The knowledge of the dielectric property is essential to design and develop microwave technology for processing biomass materials. Bamboo biomass was subjected to microwave pyrolysis, to determine the influence of each process on the yield and composition of the derived gas, oil and char products. The influence of pyrolysis temperature and heating rate for the microwave pyrolysis was investigated. A microwave-enhanced co-pyrolysis of bamboo with plastic coupled with Ni/Al2O3 catalyst was studied to produce a high yield of hydrogen-rich syngas under mild operating conditions. Ni was applied as the catalyst loaded on Al2O3 supports. The co-pyrolysis with catalyst not only produced high hydrogen amounts but also improve the quality of the liquid bio-oil. The maximum H2 content reached 54 vol% for the bamboo using activated carbon as the microwave absorbing agent with ratio of bamboo wood: Plastic at 80:20. The Ni/Al2O3 catalyst dramatically improved the gas yield as well as the hydrogen concentration. 2016 Asad Freihat, Radwan Abu-Gdairi, Hammad Khalil, Eman Abuteen, Mohammed Al-Smadi and Rahmat Ali Khan.